Mortality from nonmalignant diseases of the respiratory, genitourinary and nervous systems among workers exposed to styrene in the reinforced plastics and composites industry in the United States - Wong, O.; Trent, L. S. (Scandinavian Journal of Work, Environment & Health, 1999)
' ' OBJECTIVES ': 'Mortality from diseases of the nervous system and nonmalignant diseases of the respiratory and genitourinary systems was examined for workers exposed to styrene. Methods Altogether 15 826 styrene-exposed workers in 30 plants in the reinforced plastics and composites industry were included. Vital status was ascertained through 31 December 1989. Individual exposure estimates were developed based on job functions, existing industrial hygiene data, process changes, engineering controls, work practices, and the use of personal protective equipment. Analyses were based on cause-specific standardized mortality ratios (SMR) and the Cox proportional hazards model. Mortality data were analyzed by latency, duration of exposure, average exposure, cumulative exposure, and process category. Results For diseases of the nervous system, the SMR was 0.56 [95% confidence interval (95% CI) 0.31-0.95]. Mortality from nonmalignant genitourinary diseases was not increased (SMR 0.87, 95% CI 0.46-1.50). Latency, duration of exposure, average exposure, cumulative exposure, and process category showed no association between styrene exposure and these 2 types of disease. A small increase in mortality from nonmalignant respiratory diseases was found (SMR 1.21, 95% CI 0.98-1.47), mainly due to ``other nonmalignant respiratory diseases'' (SMR 1.40, 95% CI 1.04-1.84). The highest increase occurred for short exposure duration (SMR 1.79 for
Keywords: cohort study; epidemiology; occupational health